Cerebellar Upregulation of Cell Surface Death Receptor–Mediated Apoptotic Factors in Harmaline-Induced Tremor: An Immunohistochemistry Study. (November 2018) - Erekat, Nour S
Active caspase-3-mediated apoptosis has been implicated in the pathogenesis of harmaline-induced tremor. The aim of this study is to illustrate the impact of tremor induction on the expression of factors mediating the cell surface death receptor–dependent apoptosis. A total of 20 normal Wistar rats were randomly selected and equally divided into control and experimental groups. Tremor was induced in the experimental group by injecting the rats with a single dose of harmaline (50 mg/kg). After that, cerebellar tissues were evaluated by immunohistochemistry to examine the expression of tumor necrosis factor α (TNF-α) and active caspase-8 in the 2 groups of animals. TNF-α and active caspase-8 expression was significantly higher in cerebella from experimental rats compared with that in those from the control rats ( P value < .01). Thus, our present data suggest the association of tremor induction with the cerebellar overexpression of TNF-α and active caspase-8, correlative with Purkinje cell (PC) loss indicated by loss of calbindin immunoreactivity, indicating the induction of the cell surface death receptor–mediated apoptosis.